An attributed translation grammar for PL/0 - Salas McClyskey, Carolina Paciencia (International journal of computer mathematics, 1987)
In this paper an attributed translation grammar (abbreviated as ATG) for the PL/0 is defined. The translation achieved by the ATG is the generation of the P-codes, used in the original interpreter by Wirth [7]. Due (o backtracking which may be followed by trimming of subtrees after code generation, it is never necessary to have the complete derivation tree. This is true even with recursion.